GnRH Peptide Antagonist: Comparative Analysis of Chemistry and Formulation with Implications for Clinical Safety and Efficacy - Shikha Patel; Bhagawati Saxena; Priti Mehta; Sarfaraz K. Niazi (Pharmaceuticals)
Overexpression of the gonadotropin-releasing hormone receptor (GnRH-R) plays a vital role in the advancement of reproductive malignancies such as ovarian, endometrial, and prostate cancer. Peptidomimetic GnRH antagonists are a substantial therapeutic development, providing fast and reversible suppression of gonadotropins by directly blocking GnRH-R. Unlike typical GnRH agonists, these antagonists prevent the early hormonal flare, have a faster onset of action, and have a lower risk of cardiovascular problems. These characteristics qualify GnRH antagonists as revolutionary therapy for diseases such as advanced prostate cancer, endometriosis, uterine fibroids, and in vitro fertilization procedures. Key GnRH peptide antagonists authorized by the regulatory agencies include Cetrorelix, Ganirelix, Abarelix, Degarelix, and Teverelix. Assisted reproductive technologies (ART) are dominated by Cetrorelix and Ganirelix, while Degarelix and Abarelix have shown significant promise in treating advanced prostate cancer. Teverelix appears as a next-generation GnRH antagonist with an ideal mix of efficacy and safety, showing promise in a variety of reproductive and hormone-dependent illnesses. This review investigates the pharmacological role of GnRH in reproductive physiology and its consequences in disease, emphasizing structural advances in third- and fourth-generation GnRH antagonists. All GnRH peptide-based antagonists were analyzed in detail for formulation strategy, pharmacokinetics, effectiveness, and safety. This review also emphasizes GnRH antagonists’ clinical promise, providing insights into their evolution and the possibility for future research in developing safer, more effective treatments for complicated hormonal diseases.